2000
DOI: 10.1046/j.1365-4362.2000.00921.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA in alopecia areata

Abstract: In HLA-alopecia areata association, ethnic differences may play a role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
47
1
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 17 publications
(24 reference statements)
6
47
1
1
Order By: Relevance
“…The increased frequencies of HLA-B*27 in our study was accordant to the result from Russian [20]. In other studies, the frequencies of HLA-A1, HLA-B62 in Turkey [9], -B*12 in Finland [10], was significantly increased in AA patients compared with controls. However, we did not find these alleles were related to AA.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The increased frequencies of HLA-B*27 in our study was accordant to the result from Russian [20]. In other studies, the frequencies of HLA-A1, HLA-B62 in Turkey [9], -B*12 in Finland [10], was significantly increased in AA patients compared with controls. However, we did not find these alleles were related to AA.…”
Section: Discussionsupporting
confidence: 90%
“…No locus was merely related to early onset of AA. Kavak et al [9] found patients with juvenile onset AA showed increased HLA-Cw7 frequency, but we found the frequency of HLACw*0704 were raised in all patients no matter their onset ages. The Kuwaiti children with AA were observed to have a significant association with HLA-B21, -B40 and -B12 antigens [22], which were different from our results.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Genetic susceptibility to AA results in increased concordance rates in family members and twins, and frequent co-diagnosis with other autoimmune disorders, such as vitiligo and autoimmune thyroiditis. Genetic associations have been reported between AA and several human leukocyte antigen (HLA) genes (Colombe et al, 1995;Kavak et al, 2000;Akar et al, 2002;Entz et al, 2006;Petukhova et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…But the mechanism by which HLA-B54 is associated with these diseases has not been fully analyzed. Concerning the HLA-Cw7 antigen, no study has revealed an association between this antigen and any disease except for juvenile-onset alopecia areata [31]. It is said that the HLA-Cw7 antigen downregulates the function of non-MHC-restricted CD4+ T lymphocytes [32], but whether or not this antigen affects the pathogenesis of endometriosis is not clear at this stage.…”
Section: Discussionmentioning
confidence: 99%